Retooling : a historian confronts technological change - Williams, Rosalind H. (MIT Press, 2002)
A humanistic account of the changing role of technology in society, by a historian and a former Dean of Students and Undergraduate Education at MIT. When Warren Kendall Lewis left Spring Garden Farm in Delaware in 1901 to enter MIT, he had no idea that he was becoming part of a profession that would bring untold good to his country but would also contribute to the death of his family's farm. In this book written a century later, Professor Lewis's granddaughter, a cultural historian who has served in the administration of MIT, uses her grandfather's and her own experience to make sense of the rapidly changing role of technology in contemporary life. Rosalind Williams served as Dean of Students and Undergraduate Education at MIT from 1995 through 2000. From this vantage point, she watched a wave of changes, some planned and some unexpected, transform many aspects of social and working life--from how students are taught to how research and accounting are done--at this major site of technological innovation. In Retooling, she uses this local knowledge to draw more general insights into contemporary society's obsession with technology. Today technology-driven change defines human desires, anxieties, memories, imagination, and experiences of time and space in unprecedented ways. But technology, and specifically information technology, does not simply influence culture and society; it is itself inherently cultural and social. If there is to be any reconciliation between technological change and community, Williams argues, it will come from connecting technological and social innovation--a connection demonstrated in the history that unfolds in this absorbing book.